Auf dem Weg zu einem Modell der Translationsdidaktik - Małgorzewicz, Anna (My University, 2010)
The aim of the following article is an attempt to define the translator's competence and their role in the system of both communication and teaching transaltion. The metacognitive competence of a translator and the fundamental cognitive process talking place in their mental sysatem have been thoroughly analysed.
Keywords: Cognitive competence; Metacognitive competence of a translator; System of teaching translation; Strategies for processing language information